2017
DOI: 10.3390/s17112617
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Sentinel-1 Radar Data for the Assessment of Soil and Cereal Cover Parameters

Abstract: The main objective of this study is to analyze the potential use of Sentinel-1 (S1) radar data for the estimation of soil characteristics (roughness and water content) and cereal vegetation parameters (leaf area index (LAI), and vegetation height (H)) in agricultural areas. Simultaneously to several radar acquisitions made between 2015 and 2017, using S1 sensors over the Kairouan Plain (Tunisia, North Africa), ground measurements of soil roughness, soil water content, LAI and H were recorded. The NDVI (normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 57 publications
11
107
0
Order By: Relevance
“…As synthesized by several studies, there are different factors affecting the radar backscatter, as the C-band represents an integration of the backscatter from the ground attenuated by the canopy layer, volume scattering, and stem-ground interactions (usually negligible for wheat) [54,65,66].…”
Section: Sentinel-1 Datamentioning
confidence: 99%
“…As synthesized by several studies, there are different factors affecting the radar backscatter, as the C-band represents an integration of the backscatter from the ground attenuated by the canopy layer, volume scattering, and stem-ground interactions (usually negligible for wheat) [54,65,66].…”
Section: Sentinel-1 Datamentioning
confidence: 99%
“…In a recent study, Bousbih et al [31] investigate the sensitivity of the Sentinel-1 radar signal to soil moisture and surface roughness. For a bare soil, results showed that the radar signal in the C-band increases as soil moisture increases (5 vol.…”
Section: Real Datasetmentioning
confidence: 99%
“…The classification process was used to discriminate between irrigated and non-irrigated fields. Two classifications were used (Bousbih et al, 2018). The first one concerns the SVM classification to delineate between the irrigated and rainfed agricultural fields, using the means and variance soil moisture time series.…”
Section: Approach Based On Satellite Productsmentioning
confidence: 99%
“…The retrieved accuracy of estimated volumetric soil moisture is about 5 vol.%. Based on estimated moisture products, two methodologies are considered to map irrigated areas , Bousbih et al, 2018. An analysis of different metrics (mean, variance, correlation length, etc.)…”
mentioning
confidence: 99%